Dekat Bau Bangkai Jauh Bau Wangi Studi pada Pasangan Suami Istri yang Tinggal Serumah dengan Orang Tua - Suniyah, Siti Arah; Haris, Hasnawi; Awaru, Andi Octamaya Tenri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to identify the contributing factors, impacts, and resilience strategies of married couples who live with their parents. This research employs a qualitative method with a library research approach, where data from books, indexed journals, and scientific articles were analyzed using content analysis techniques. The findings show that conflicts mainly arise from overlapping roles and authority, generational differences in values and lifestyles, economic dependence, loss of privacy, and communication barriers. These conditions lead to emotional tension, reduced marital harmony, limited autonomy for the couple, and an imbalance between the nuclear family and the extended family. The solutions identified include resilience strategies such as assertive and empathetic communication, establishing clear role boundaries, strengthening economic independence, social support and value adaptation, and fostering intergenerational empathy. This study highlights the importance of balancing emotional closeness and autonomy to maintain harmony among couples living with their parents.